Replication Data for: Assessing high-impact spots of climate change: spatial yield simulations with Decision Support System for Agrotechnology Transfer (DSSAT) model - Eitzinger, Anton; Läderach, Peter R.D.; Rodríguez Sánchez, Beatriz; Fisher, Myles J.; Beebe, Stephen E.; Sonder, Kai; Schmidt, Axel (International Center for Tropical Agriculture, 2016)
Data were collected by a simulation model to estimate yield changes due to climate change in El Salvador, Guatemala, Honduras and Nicaragua. We analysed the simulated yield changes to spatially classify high-impact spots of climate change across the four countries. We identified hot spots, adaptation spots and pressure spots for drybeans production in the study area and derived three main recommendations.